Identification key, diversity and host associations of parasitoids (Hymenoptera: Braconidae: Aphidiinae) of aphids attacking cereal crops in Egypt - Gadallah, Neveen S.; El-Heneidy, Ahmed H.; Mahmoud, Samar M.; Kavallieratos, Nickolas G. (Zootaxa, 2017)
In the present study, a total of eleven Aphidiinae parasitoid species belonging to six genera (Aphidius Nees, Binodoxys Mackauer, Diaeretiella Starý, Ephedrus Haliday, Lysiphlebus Foerster and Praon Haliday) were recorded from three aphid species [Rhopalosiphum maidis (Fitch), Rhopalosiphum padi (L.) and Sitobium avenae (F.)] feeding on four cereal plants (Avena sativa L., Hordeum vulgare L., Triticum aestivum L. and Zea mays L.) in Egypt. An illustrated key of the recorded aphidiines, the tritrophic (parasitoid-aphid-plant) associations and their distribution in the target area are also provided. Among the emerged parasitoids, Aphidius ervi Haliday is a new record for the fauna of Egypt. Aphidius transcaspicus Telenga and Binodoxys angelicae (Haliday) are reported for the first time to be associated with aphids infesting cereals in Egypt.